Mengkaji Tahap Keberkesanan Rekabentuk Antaramuka Dalam Pembangunan Laman Web - Carelo, Rejos (Universiti Malaysia Sarawak (UNIMAS), 2004)
Generally, this project serve the purpose of looking into the significant of interface designing in website development using multimedia and also redesign the website for Sentose Hospital. In details, this report will indentify the importance of various multimedia elements as factors in designing interface for development of an effective website. There are six propositions to be analyze in this research which are (1) bright combination of the interface background and using less design pattern for the comort of the users (2) arrangment of information according to its priority in the middle of the interface display (3) simple, understandable and consistent arrangment of icons in every webpage (4) suitable usage of font size and text consistently as to be easily comprehend (5) animations as an attraction and making the sites more interactive and (6) simple yet attractive graphics for the comfort of users. This website was also construct by using the Waterfall model. A sample invoving 30 respondent of the hospital staffs and also visitors from outside was made. The data retrieved was analyze using Statistical Package for Social Science (SPSS) software. The result is then being discussed and elaborated using descriptive analysis according to its frequencies (n) and percentage (%). As a conclusion, the propositions made for developing the interface design for this website are important in creating an attractive and effective information displays. All of the propositions made show significant relationship with effective interface design. As for that, the propositions made are suitable as prerequisites for developing an attractive and effective websites